2023
DOI: 10.1021/acs.inorgchem.3c00917
|View full text |Cite
|
Sign up to set email alerts
|

Photogenerated Ni(I)–Bipyridine Halide Complexes: Structure–Function Relationships for Competitive C(sp2)–Cl Oxidative Addition and Dimerization Reactivity Pathways

Abstract: We report the facile photochemical generation of a library of Ni(I)−bpy halide complexes (Ni(I)( R bpy)X (R = t-Bu, H, MeOOC; X = Cl, Br, I) and benchmark their relative reactivity toward competitive oxidative addition and off-cycle dimerization pathways. Structure−function relationships between the ligand set and reactivity are developed, with particular emphasis on rationalizing previously uncharacterized ligand-controlled reactivity toward high energy and challenging C(sp 2 )−Cl bonds. Through a dual Hammet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 65 publications
3
50
0
Order By: Relevance
“…Complexes 17 and 18 are the first structurally characterized monomeric t ‑Bu bpy-bound Ni I complexes. The nuclearity of similar complexes is observed to be crucial to their reactivity: dimeric [( t ‑Bu bpy)­Ni I X] 2 species (X = Cl, Br) cannot kinetically disaggregate and therefore are inert toward aryl halides (Figure A), whereas in situ generated monomeric ( t ‑Bu bpy)­Ni I X species have been shown to activate even aryl chlorides . Indeed, 17 and 18 are capable of activating aryl halide bonds (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Complexes 17 and 18 are the first structurally characterized monomeric t ‑Bu bpy-bound Ni I complexes. The nuclearity of similar complexes is observed to be crucial to their reactivity: dimeric [( t ‑Bu bpy)­Ni I X] 2 species (X = Cl, Br) cannot kinetically disaggregate and therefore are inert toward aryl halides (Figure A), whereas in situ generated monomeric ( t ‑Bu bpy)­Ni I X species have been shown to activate even aryl chlorides . Indeed, 17 and 18 are capable of activating aryl halide bonds (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…The nuclearity of similar complexes is observed to be crucial to their reactivity: dimeric [( t-Bu bpy)Ni I X] 2 species (X = Cl, Br) cannot kinetically disaggregate and therefore are inert toward aryl halides (Figure 8A), 22 whereas in situ generated monomeric ( t-Bu bpy)Ni I X species have been shown to activate even aryl chlorides. 39 Indeed, 17 and 18 are capable of activating aryl halide bonds (Figure 8B). Furthermore, complex 18 is an especially useful Ni I model system for mechanistic and stoichiometric studies: it has a direct Ni 0 analogue, 19, against which its reactivity can be evaluated.…”
Section: Implications Of Bulky Monophosphine Speciation At Ni I In Cr...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, one of our groups has recently provided detailed electronic structural and mechanistic studies of the ground- and excited-state properties of low-spin Ni II bipyridine aryl halide complexes and their Ni I photogenerated intermediates. These studies identified key structure–function relationships relevant to excited-state bond homolysis and oxidative addition reactivity, which allowed for the mechanistic analysis of Ni I -mediated activation of strong C­(sp 2 )–Cl bonds. , Our groups also recently participated in collaborative work that utilized cyclic voltammetry under catalytic conditions and UV–vis–NIR spectroelectrochemistry to better understand the interplay of Ni and Cr-oxidation states for Nozaki–Hiyama–Kishi coupling . Another study by Neidig et al utilized a combination of Mössbauer spectroscopy, magnetic circular dichroism, and computations to demonstrate that the kinetic competency of four-coordinate organoiron toward halogen abstraction is dependent on the accessibility and relative energy of iron-based orbitals …”
Section: Introductionmentioning
confidence: 99%